Survival strategies for the sustainable livelihoods of migrant youth in Musina Town, RSA : a case of refugees in refugee shelters managed by churches - Ramoshaba, Dillo Justin (My University, 2021)
Southern Africa encounters an exceptional international human mobility. Several studies view South Africa as a host country for a large number of immigrants, particularly migrant youth who come from other African countries. Upon their arrival in South Africa, studies show that migrant youth encounter a vast number of challenges such as being excluded from welfare services of South Africa. It is from this background that this study sought to explore survival strategies that migrant youth in Musina Town employ for their sustainability. This study presents qualitative findings on the survival strategies employed by migrant youth in Musina Town, Limpopo Province of South Africa. Ten migrant youth in Musina Town who are accommodated in shelters managed by churches were used as a case study and were purposively and conveniently selected to participate in the study. Data was collected through face to face semi-structured interviews and analysed thematically through the assistance of the Nvivo software. The resilience, neoclassical and network theories were used to guide the study. However, the resilience theory served as the over-arching theory of the study as it is more relevant and appropriate in explaining how migrant youth bounced back to normality after the hardships they experienced in South Africa. Findings reveal that bad economic conditions from countries of origin pushed young people to South Africa for better livelihoods. However, due to lack of funds, some crossed borders fraudulently for their survival. Upon their arrival in South Africa, findings further revealed that some migrant youth engage in criminal acts to make a living. It was also found that some migrant youth are involved in sex work to make a living. Social networking with their counterparts, street vending, cheap and exploitative labour were also found to be strategies employed by migrant youth for their sustainable livelihoods. It is thus concluded that migrant youth in South Africa are exposed to bad conditions upon their arrival in the country for their sustainable livelihoods. Findings also reveal various coping strategies that migrant youth employ to mitigate their exclusion from South African welfare services. Recommendations which include integrated intervention and future research are provided in this study
Thesis (M. A. (Social Work)) -- University of Limpopo, 2021
Keywords: International human mobility; Immigration; Welfare services South Africa; Musina Town; Refugees shelter; Youth -- Social conditions -- South Africa; Migrant labor -- Social conditions -- South Africa; Refugees